Remasking of Candida albicans β-Glucan in Response to Environmental pH Is Regulated by Quorum Sensing - Fabien Cottier (American Society for Microbiology, 2019)
ABSTRACT Candida albicans is a commensal yeast of the human gut which is tolerated by the immune system but has the potential to become an opportunistic pathogen. One way in which C. albicans achieves this duality is through concealing or exposing cell wall pathogen-associated molecular patterns (PAMPs) in response to host-derived environment cues (pH, hypoxia, and lactate). This cell wall remodeling allows C. albicans to evade or hyperactivate the host’s innate immune responses, leading to disease. Previously, we showed that adaptation of C. albicans to acidic environments, conditions encountered during colonization of the female reproductive tract, induces significant cell wall remodeling resulting in the exposure of two key fungal PAMPs (β-glucan and chitin). Here, we report that this pH-dependent cell wall remodeling is time dependent, with the initial change in pH driving cell wall unmasking, which is then remasked at later time points. Remasking of β-glucan was mediated via the cell density-dependent fungal quorum sensing molecule farnesol, while chitin remasking was mediated via a small, heat-stable, nonproteinaceous secreted molecule(s). Transcript profiling identified a core set of 42 genes significantly regulated by pH over time and identified the transcription factor Efg1 as a regulator of chitin exposure through regulation of CHT2. This dynamic cell wall remodeling influenced innate immune recognition of C. albicans, suggesting that during infection, C. albicans can manipulate the host innate immune responses. IMPORTANCE Candida albicans is part of the microbiota of the skin and gastrointestinal and reproductive tracts of humans and has coevolved with us for millennia. During that period, C. albicans has developed strategies to modulate the host’s innate immune responses, by regulating the exposure of key epitopes on the fungal cell surface. Here, we report that exposing C. albicans to an acidic environment, similar to the one of the stomach or vagina, increases the detection of the yeast by macrophages. However, this effect is transitory, as C. albicans is able to remask these epitopes (glucan and chitin). We found that glucan remasking is controlled by the production of farnesol, a molecule secreted by C. albicans in response to high cell densities. However, chitin-remasking mechanisms remain to be identified. By understanding the relationship between environmental sensing and modulation of the host-pathogen interaction, new opportunities for the development of innovative antifungal strategies are possible.